Parâmetros biológicos de Protortonia navesi (Hemíptera:Monophlebiidae) em diferentes variedades de mandioca (Manihot esculenta, Crantz) - Prestes, Tânia Mari Vicentini (2014)
Cassava is cultivated in all regions of Brazil, being the South an important producer of starch, especially in Paraná, which holds 71% of the national amount. In this state, the cultivation is carried out in monoculture, in large areas and using broad-spectrum chemicals, leading in recent years, to an increase of plagues related to this culture, such as cochineal, especially Protortonia navesi. Considering the increase in the occurrence of this species, the aim of this study was to evaluate the biological and morphological parameters of this insect in roots of different varieties of cassava, being the biology and morphology studied in Santa Helena and the comparison of biological parameters among the Cascuda, Baianinha, IAC 90 and Santa Helena. The research was carried out in the Biological Control Laboratory at the State University of West Paraná, UNIOESTE, in Marechal Cândido Rondon, PR, on cassava plants of Santa Helena, Cascuda, Baianinha and IAC 90 varieties. They were removed and replanted in field trays, leaving the tuberous roots portions exposed on soil surface. Cages were fixed over the roots and inside them, a nymph was placed within a day of live, and which was observed daily to obtain the biological parameters. The experimental design was completely randomized. The following biological parameters were evaluated: Instar duration, pre-oviposition, oviposition, fecundity, fertility and embryonic period, survival and morphological characteristics. A fertility life chart was elaborated from data using Tabvida software. To the evaluation of Protortonia navesi biological parameters in different varieties of cassava, the obtained data was analyzed with the aid of Genes app, which underwent to Liliefors analysis and analysis of variance (F test), being the averages compared by the Tukey test at 5% probability. The average life spans of the first, second and third instars were 18, 11.5 and 18.1 days respectively. The pre-oviposition, oviposition and post-oviposition periods were of 4.7, 20.9 and 0.97 days respectively. The reproductive rate was 204 females per female; the capacity of population growth was 0.088; the time to complete a generation was 60.43 days; the finite rate of population growth was 1.09 individuals per day and the time to double the population was 7.88 days. There were differences among the varieties for the parameters of nymph, pre-oviposition, oviposition and fecundity periods. The highest mortality occurred in the first instar of IAC 90 variety. It was observed that IAC 90 interfered in the development of Protortonia navesi, however, further studies are necessary to identify the plant substances that interact in the development of cochineal, as well as studies that provide free choice of the insect to the plant